Far beyond the motor neuron: the role of glial cells in amyotrophic lateral sclerosis - Paulo Victor Sgobbi de Souza; Wladimir Bocca Vieira de Rezende Pinto; Flávio Moura Rezende Filho; Acary Souza Bulle Oliveira (Arquivos de Neuro-Psiquiatria)
ABSTRACT Motor neuron disease is one of the major groups of neurodegenerative diseases, mainly represented by amyotrophic lateral sclerosis. Despite wide genetic and biochemical data regarding its pathophysiological mechanisms, motor neuron disease develops under a complex network of mechanisms not restricted to the unique functions of the alpha motor neurons but which actually involve diverse functions of glial cell interaction. This review aims to expose some of the leading roles of glial cells in the physiological mechanisms of neuron-glial cell interactions and the mechanisms related to motor neuron survival linked to glial cell functions.